Ribonucleoproteins of Uukuniemi virus are circular. - Pettersson, R F (1975)
The internal ribonucleoprotein (RNP) of Uukuniemi virus was released with Triton X-100 and analyzed on sucrose gradients. Three species of RNP sedimenting at 140 to 150, 105 to 120, and 85 to 90S could be separated. All of them contained the same ratio of core polypeptide (mol wt, 25,000) to RNA. Eelctron microscopy using rotatory shadowing showed that all three species were circular. Free ends were rarely seen. Measurements of the strands revealed three distinct length classes of about 2.8, 1.4 and 0.7 mu m. Polyacrylamide-agarose gels showed that the largest RNP contained the L RNA, the medium-sized RNP the M RNA, and the smallest RNP the S RNA.